The determinants of demand for micronutrients: an analysis of rural households in Bangladesh - Bouis, Howarth E.; Novenario-Reese, Mary Jane G. (International Food Policy Research Institute, 1997)
Micronutrient deficiencies are particularly severe in Bangladesh. Understanding howhousehold income, food prices, parental education and nutritional knowledge, and culturally-based customs and food preferences interact to determine food consumption patterns (particularly for nonstaple foods), and so micronutrient intake, can provide crucial information for designing policies and intervention programs to improve human nutrition. Within the typical dietary patterns of the Bangladeshi survey population, the key food group with respect to micronutrient consumption is vegetables, providing nearly 95 percent of vitamin A intake, 75 percent of vitamin C intake, and 25 percent of iron intake. Vegetables are the least expensive sources of all of these nutrients. Vegetables are sufficiently inexpensive sources of vitamin A and vitamin C that they could provide the RDA within normal dietary patterns and the budgets of low-income groups. There is no corresponding inexpensive source of iron. Programs to educate consumers about the importance of meeting recommended daily allowances of vitamin A and vitamin C and about commonly eaten sources of these nutrients has the potential for improving intake. Because a high proportion of vitamin A and vitamin C intake apparently comes from own-production, extension programs to promote growing specific vitamin A and vitamin C rich foods not only would provide households with a ready supply of these nutrients, but increased production could bring the local price down.